Analisis Faktor-faktor yang Memengaruhi Keputusan Pembelian pada Bunga Krisan Potong di Pasar Bunga Bandungan Kabupaten Semarang - Fadlila, Tsania Noor; Setiyawan, Hery; Ekowati, Titik (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The growing number of cut chrysanthemum farmers in Bandungan District has intensified competition in the flower market. This study investigates 1) to identify the characteristics of consumers who purchase cut chrysanthemums at Bandungan Flower Market  2) the influence of product quality, service quality, income, price, and consumer preferences on purchasing decisions for cut chrysanthemums at Bandungan Flower Market, Semarang Regency. A survey was conducted in March–April 2025 involving 120 respondents, selected through accidental sampling. Data were analyzed using descriptive statistics and binary logistic regression with SPSS 25. The results indicate that most consumers are female, aged 21–30 years, with senior high school education, an income range of IDR 2,234,953–3,435,464, and a purchasing frequency of twice. The model fit test yielded a chi-square value of 1.403 and a Nagelkerke R square of 0.833, suggesting a strong explanatory power of the model. The omnibus test showed a chi-square value of 84.048, confirming that the examined factors jointly affect purchasing decisions. Further analysis using the Wald test revealed that product quality, consumer preferences, price, and income significantly influence purchasing decisions, whereas service quality has no significant effect. These findings highlight the importance of improving product attributes and aligning with consumer preferences to enhance competitiveness in the cut chrysanthemum market.